IMPACT OF GOVERNMENT POLICIES ON MSME GROWTH: EVALUATING EFFECTIVENESS AND GAPS - Saxena, Sonakshi; Sirohi, Prof. Rajeev Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are pivotal to the economic growth and development of nations. They contribute significantly to employment generation, industrial output, and exports. Recognizing their importance, governments worldwide have implemented various policies to foster the growth and sustainability of MSMEs. However, the effectiveness of these policies often varies, revealing gaps that need addressing. This paper evaluates the impact of government policies on MSME growth, analyzing their effectiveness and identifying existing gaps through a global and regional lens. Recommendations for bridging these gaps and enhancing policy frameworks are also proposed.